Characteristics of emotional disturbance of female and male students in elementary, middle, and high school. Issue 3 (20th September 2022) - Cullinan, Douglas; Lambert, Matthew C.; Epstein, Michael H.
Abstract: Provide data on the five characteristics of emotional disturbance (ED). For 503 students with ED and 2016 without disabilities, teachers rated the characteristics ( Inability to Learn ; Relationship Problems ; Inappropriate Behavior ; Unhappiness or Depression ; Physical Symptoms or Fears ), plus Socially Maladjusted . We applied a 2 (ED, without disabilities) × 2 (female, male) × 3 (elementary, middle, high school) covariance analysis, with follow‐up comparisons. Students with ED showed greater problems than students without disabilities on all five characteristics, and Socially Maladjusted . On Inability to Learn, among students with ED genders did not differ at elementary but males had greater problems at middle school. On Inappropriate Behavior and Physical Symptoms or Fears, students with ED varied across school levels but students without disabilities did not. All five characteristics discriminated students with ED from those without disabilities. Differences between genders and school levels varied across characteristics. Practitioner points: On all five IDEA characteristics of emotional disturbance (ED), students with ED show significantly more serious problems than their peers with no disabilities. Assessment of all five characteristics of ED can help the multidisciplinary team determine whether a student qualifies as ED. Assessment of the five characteristics can also suggest directions for school intervention.